4x - 2x + 8 = 6(x + 4) Given
(4x - 2x) + 8 = 6(x + 4)
2x + 8 = 6(x + 4) Combine like terms
2x + 8 = (6)(x) + (6)(4)
2x + 8 = 6x + 24 Distributive Property
2x - 6x + 8 = 6x - 6x + 24
-4x + 8 = 24 Subtraction Property of Equality
-4x + 8 - 8 = 24 - 8
-4x = 16 Subtraction Property of Equality
-4x : (-4) = 16 : (-4)
x = -4 Division Property of Equality
Answer:
3z-44
Step-by-step explanation:
All you have to do is to simplify the numbers. 2 + 6 - 52 = -44.
T b
0 70
1 66
2 62
3 58
4 54
This is not a proportional relationship because the ratios are not equivalent.
1/66 (t/b) is not equivalent to 2/62 (t/b).
It will be 20*21 based on the pattern in the chart